THE RIGHT TO HEALTH AS A NATURAL HUMAN RIGHT - Risteski, Temelko; Spirkoska, Biljana; Spirkoska, Ana (Institute of knowledge management, 2023)
The basis of the right to health is health as a natural state of human personality. From a sociological point of view, the right to health is a human social right. As a social right, the right to health is the right to have health as a natural state of human being. The main goal of this paper is to perceive the legal nature of the right to health as a human right through the prism of natural law theory and on the basis of international normative acts on human rights, such as: Universal Declaration of Human Rights, International Covenant on Economic, Social and Cultural Rights, European Social charter, Convention on the Rights of the Child, etc. In the paper the method of content analysis of the mentioned international normative acts is used. The analysis is based on the legal-philosophical assumptions of the theory of natural law. According this theory all human beings are born free and equal in dignity and rights. This theory is an ideological source of most international normative acts on human rights. The analysis of international normative acts on human rights enables a comprehensive overview of the international legal foundations of the right to health as a natural human right, on which the national legislation of individual countries on the protection of citizens' health is based. Among them is national legislation on health protection of the Republic of North Macedonia. International normative acts on human rights as the Universal Declaration of Human Rights and other above named represent a quality normative-legal basis for the establishment of national normative regulations on health protection citizens based on the legal-philosophical foundations of the theory of natural law. According to this theory, the right to health is an innate human right, which in the practice of normative regulation of the rights of citizens of individual countries is treated as the right to the highest standard of physical and mental health. Constitution of the Republic of North Macedonia guarantees the citizens of the Republic the right to health care. According the Constitution citizens have the right and duty to protect and promote their own health and the health of others. On the basis of the Constitution, several laws have been adopted for the health care of the citizens of the Republic.